The LTA project: Bridging the gap between training and the profession in real-time intralingual subtitling - Eugeni, Carlo; Bernabé Caro, Rocío (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2020)
Real-time intralingual subtitles enable access to live audiovisual products. However, the provision and the quality of such services across Europe is uneven and sometimes insufficient because live subtitlers are untrained or only partially trained and without recognized professional status. To bridge this gap, the EU-funded project Live Text Access (LTA) aims to create ad-hoc training materials and propose the recognition of certified professionals. This article first concentrates on the multifaceted and heterogeneous terminology adopted in the field. Then it provides an overview of the current situation in which live subtitlers are trained in Europe, focusing on the LTA rationale for creating open-source training materials based on certification, subtitling standards and a user-oriented approach. Finally, it reports on the progress the project has made in defining both the professional profile and the skills and competences of the intralingual real-time subtitler.